2020
DOI: 10.3389/fpubh.2020.00191
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Issues of Intelligent Assistive Technology Use Among People With Dementia and Their Caregivers: A U.S. Perspective

Abstract: The increasing number of older adults with cognitive deficits, including dementia, poses a major challenge for public health in the United States. At the same time, the limited number of informal and professional caregivers available to support this rapidly growing population is of mounting concern. Not only does population aging limit the number of potential caregivers, but extant caregivers often lack skills to provide quality care. The integration of intelligent assistive technologies (IAT), including devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…From our analyses, we have demonstrated that the adapted TAM2 concepts of caregivers provide support for our hypotheses about care recipients’ use of fall alert wearables, which is reflective of previous literature [ 12 , 20 - 25 , 30 ]. Our model demonstrated that both high perceived usefulness and value of technology for caregiving was associated with greater interest in technologies for caregiving and that greater interest in technology for caregiving was predictive of greater use of fall alert wearables among care recipients, although only 28% (153/548) of our study’s care recipients used fall alerts.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…From our analyses, we have demonstrated that the adapted TAM2 concepts of caregivers provide support for our hypotheses about care recipients’ use of fall alert wearables, which is reflective of previous literature [ 12 , 20 - 25 , 30 ]. Our model demonstrated that both high perceived usefulness and value of technology for caregiving was associated with greater interest in technologies for caregiving and that greater interest in technology for caregiving was predictive of greater use of fall alert wearables among care recipients, although only 28% (153/548) of our study’s care recipients used fall alerts.…”
Section: Discussionsupporting
confidence: 81%
“…Of particular interest is the growing market for fall alert systems, which are intended to help older adults reduce fear of falling and stay independent by ensuring that help will be available in the event of a fall. There is now a plethora of medical alert systems with fall detection, and while there are market comparisons and a growing amount of literature on older adults' acceptance of technology, less is known about how caregivers' attitudes toward technology can impact care recipients' use of such technology [6,[8][9][10][11][12]16,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…From our analyses, we have demonstrated that the adapted TAM2 concepts of caregivers provide support for our hypotheses about care recipients' use of fall alert wearables, which is reflective of previous literature [12,[20][21][22][23][24][25]30]. Our model demonstrated that both high perceived usefulness and value of technology for caregiving was associated with greater interest in technologies for caregiving and that greater interest in technology for caregiving was predictive of greater use of fall alert wearables among care recipients, although only 28% (153/548) of our study's care recipients used fall alerts.…”
Section: Principal Findingssupporting
confidence: 80%
“…However, despite some enthusiastic reports ( 67 ), findings are generally mixed. One limitation of technological applications is the inability to train caregivers on the use of computer-based support strategies ( 68 ) due to lockdown-related restrictions or a lack of skilled staff in nursing homes. Caregivers are required to address the needs of the user and the user’s acceptance of technology ( 14 ).…”
Section: Discussionmentioning
confidence: 99%